Identification of solamargine as a cisplatin sensitizer through phenotypical screening in cisplatin-resistant NSCLC organoids - Han, Yi; Shi, Jianquan; Xu, Ziwei; Zhang, Yushan; Cao, Xiaoqing; Yu, Jianhua; Li, Jie; Xu, Shaofa (Frontiers in Pharmacology, 2022)
Although Cisplatin (DDP) is a widely used first-line chemotherapy medication, DDP resistance is one of the main causes of treatment failure in advanced lung cancer. Therefore, it is urgent to identify DDP sensitizers and investigate the underlying molecular mechanisms. Here we utilized DDP-resistant organoids established from tumor biopsies of patients with relapsed lung cancers. In this study, we identified Solamargine as a potential DDP sensitizer through screening a natural product library. Mechanically, Solamargine induced G0/G1-phase arrest and apoptosis in DDP-resistant lung cancer cell lines. Gene expression analysis and KEGG pathway analysis indicated that the hedgehog pathway was suppressed by Solamargine. Moreover, Gli responsive element (GRE) reporter gene assay and BODIPY-cyclopamine binding assay showed that Solamargine inhibited the hedgehog pathway via direct binding to SMO protein. Interestingly, Solamargine and DDP showed a synergetic effect in inhibiting DDP-resistant lung cancer cell lines. Taken together, our work herein revealed Solamargine as a hedgehog pathway inhibitor and DDP-sensitizer, which might provide a new direction for further treatment of advanced DDP-resistant lung cancer patients.